PENGEMBANGAN MODEL PEMBELAJARAN GERAK DASAR MANIPULATIF PADA SISWA KELAS VSEKOLAH DASAR - Ramadhan, Ikhsan (Tren Terbaru Dalam Penelitian dan Penelitian Bidang Olahraga, 2017)
In general the purpose of this research is to improve the results of student learning through the development of learning model of throw in elementary school class IV SD. In addition to this research was conducted how to obtain information in depth about the development learning model of long jump in elementary school students. This study uses a Model development. The subject in this study is the grade IV SD. This research was conducted with the 7 steps, the first step is to determine an idea that will be developed, both making learning the game, the third model draft is revising product. It conducted by the experts concerned, the fourth product prototype made with the real games practical model, the fifth test prototype, is testing of the subject field in both trials phase I or phase II and then revised again experts in order to produce the perfect product, the seventh and last is the refinement of products to reach the expected end product development. The stages are then obtained as a result of such research to the analysis of the evaluation of the first phase with 45 products generated a total of 565 respondents with a score total overall score of 588 respondents so it can be in percentage 56,5 %, and based on the evaluation of the phase II analysed by using the final product 42 were then generated a total score of respondents 740 and total overall score, and the percentage is 74  thus the criteria is Valid.     Based on the results of the research it can be concluded that: (1) learning model of motion elementary throw with games, elementary school students is urgently needed by the teacher fisical education as well as being able to increase the learning effectively and efficiently. (2) with the model of learning that has researchers develope, students are more motivated and active in following the process of learning.